TAMPILAN KEKERASAN DALAM FILM (Studi Analisis Isi Tentang Kekerasan Fisik dan Psikologis Dalam Film“The Raid: Redemption” Karya Gareth Evans) - Ezzy Augusta (FLOW, 2013)
This research contains a study using descriptive analysis with a quantitative approach regarding physical violence and psychological violence the film The Raid: Redemption. The Raid: Redemption is a film directed by Gareth Evans, one of the famous American director. This movie tells the story of the ambush attack that carried out by special forces on the safe house of criminals. This study focuses on the study of media content which has film has quantitative feature. This study used the paradigm of positivistic approach. Where as for the instrument of data analysis,  researchers used content analysis technique by Holsti. In this study, researchers tried to examine how physical violence and psychological violence shown in the film The Raid: Redemption. Researchers examined the research object taken from physical violence and psychological violence contained in the film The Raid: Redemption. The percentage of inter-coder reliability test of physical violence as follows: Hit 99%; slap 67%; strangling 93%; kicks 99%; throw 93%; wounding 98%; maul 89%; kill 95%. While inter-coder reliability psychological violence showed by the following : yelling 91%; swear 98%; threatens 90%; degrading 87%; manage 81%; harassing 96%; stalking 80% and spying 100%. Keywords: Content Analysis, Physical Violence, Psychological Violence, The Raid: Redemption.